'It depends': Characterizing speech and language therapy for preschool children with developmental speech and language disorders. Issue 6 (17th September 2019) - Morgan, Lydia; Marshall, Julie; Harding, Sam; Powell, Gaye; Wren, Yvonne; Coad, Jane; Roulstone, Sue
Abstract: Background: Several studies have suggested that practitioners hold speech and language therapy (SLT) practice as tacit and consequently it is difficult for the therapist to describe. The current study uses a range of knowledge elicitation (KE) approaches, a technique not used before in SLT, as a way of accessing this tacit knowledge. There is currently no agreed framework that establishes key factors underpinning practice for preschool children with speech and language disorders. This paper attempts to address that gap. Aims: To develop a framework of SLTs' practice when working with preschool children with developmental speech and language disorders (DS&LD). Methods & Procedures: A mixed‐methods approach was adopted for this study. Data were collected iteratively, from 245 SLTs with experience of working with preschool children with DS&LD across sites in England, by means of focus groups and national events. There were three stages of data collection: local sites, specific‐interest groups and two national events. KE techniques were used to gather data, with initial data being collected in local site focus groups. Findings from groups were taken to subsequent larger groups where a combination of concept mapping, teach‐back and sorting exercises generated a more detailed description of practice, using discussion of consensus and disagreement to stimulate further exploration and definition and provide validatory evidence. Outcomes & Results: This paper provides a high‐level framework of therapy for preschool children with DS&LD that makes practice explicit in this area. The framework proposes that therapists' aims for this group of children fall into three categories: addressing children's areas of impairment and skills; achieving functionally meaningful skills and carryover; and supporting adults to provide a supportive communication environment. The exact configuration is shaped by the child's context and needs. Conclusions & Implications: The framework highlights themes that are well researched in the literature (e.g., speech) and others that have been little studied (e.g., adult understanding), indicating a disconnect between research evidence and practice. The research also highlights the complex nature of interventions for preschool children with DS&LD and the importance therapists attribute to tailoring therapy to individual needs. The framework provides a scaffold upon which SLTs can focus their clinical practice and encourages the profession to understand and explore better the gaps between research evidence and clinical practice for preschool children with DS&LD.